TAJDÎD FIQH DARI KONSERVATIF TEKSTUAL MENUJU FIQH PROGRESIF KONTEKSTUAL - Nasrulloh, Nasrulloh (De Jure: Jurnal Hukum dan Syari'ah, 2014)
By reference to Rule (al-mashaqqah  tajlib al-Taysir) and  (idza dhaqa  ittasa'a), the need  to  reconstruct  the fiqh through tajdîd considered a necessity when there are difficulties to implement it. On one side there is an opinion  that  tajdîd  should be limited to new problems that are not listed in  the qath'i texts, but on  the other hand argue that all texts are dzanni, so there is no limit in the realm of tajdîd and ijtihad. Through  this theme, the authors also cite some of the thinking that distinguishes between authenticity of the revelation as the God‟s will and the authenticity of Hadis which  is still questionable. Then, a distinction efforts also should be made between the revelation of God's will as an ideal and the truth of human understanding (fiqh) that is relative so it needs to be reconstructed in order to remain relevant anywhere and anytime.